From the experience of forming research competence in independent work of students in process of studying history of Russia - M. I. Mashkarin (Омский научный вестник: Серия "Общество. История. Современность")
The article describes the analysis of the experience of organizing a written homework assignment on the topic «My relatives in the Great Patriotic War of 1941–1945» by the students of the first courses of OmSTU. The paper shows that the traditional approach, which exists in many universities, on writing essays on various topics on the history of Russia on the basis of the literature read has become obsolete under the prevalence of the Internet. In these conditions, in order to form competencies for students in the study of the history of Russia, it is necessary to develop the skills to identify the historical problems necessary for studying, the ability to organize the collection of materials for the disclosure of the topic, to analyze the materials and structure it, and draw correct general conclusions